Development of a multienzyme isothermal rapid amplification and lateral flow dipstick combination assay for bovine coronavirus detection - Ji, Chengyuan; Feng, Yiqiu; Sun, Ruini; Gu, Qibing; Zhang, Yao; Ma, Jiale; Pan, Zihao; Yao, Huochun (Frontiers in Veterinary Science, 2023)
Bovine coronavirus (BCoV) is a major cause of infectious disease in cattle, causing huge economic losses to the beef and dairy industries worldwide. BCoV can infect humans and multiple other species of animals. A rapid, reliable, and simple test is needed to detect BCoV infection in suspected farms. In this study, we developed a novel multienzyme isothermal rapid amplification (MIRA) and lateral flow dipstick (LFD) combination assay, targeting a highly conserved region of the viral nucleocapsid (N) gene for BCoV detection. The MIRA-LFD assay was highly specific and sensitive, comparable to a published reverse transcription quantitative PCR (RT-qPCR) assay for BCoV detection. Compared with the published RT-qPCR assay, the κ value of the MIRA-LFD assay in the detection of 192 cattle clinical samples was 0.982. The MIRA-LFD assay did not require sophisticated instruments and the results could be observed with eyes. Our results showed that the MIRA-LFD assay was a useful diagnostic tool for rapid on-site detection of BCoV.